(untitled) (Conference Zone, 2022)
Cesarean section is becoming increasingly high worldwide. Especially in middle-income and high-income countries. Although, vaginal delivery natural process some women prefer give a birth by means of Cesarean section (CS) keeping in mind it’s less stressful. However Cesarean section could be even more stressful and have a lot of side- effects life-saving for both fetus and mother only when there are some strong medical indications. In past two decades CS rate witnessed rapid rise without any clear justified clinical indications or rationale and now account for nearly one third of births [Robson M. The ten group classification system (TGCS) - a common starting point for more detailed analysis. BJOG: Int J Obstet Gy 2015.] Furthermore, World Health Organization (WHO) has declared that the optimal cesarean delivery rate should be 10-15%, [World Health Organization. World health statistics 2015. World Health Organization, 2015.] The Robson 10-group Classification System (TGCS) was developed with the aim of auditing and potentially reducing the rate of cesarean section. [Begum T, Nababan H, Rahman A, et al. Monitoring caesarean births using the Robson ten group classification system: a cross-sectional survey of private forprofit facilities in urban Bangladesh. PLoS One 2019;]